The Resistance of Oilseed Rape Microspore-Derived Embryos to Osmotic Stress Is Associated With the Accumulation of Energy Metabolism Proteins, Redox Homeostasis, Higher Abscisic Acid, and Cytokinin Contents - Urban, Milan O.; Planchon, Sébastien; Hoštičková, Irena; Vanková, Radomira; Dobrev, Peter; Renaut, Jenny; Klíma, Miroslav; Vítámvás, Pavel (Frontiers in Plant Science, 2021)
The aim of the present study is to investigate the response of rapeseed microspore-derived embryos (MDE) to osmotic stress at proteome level. The PEG-induced osmotic stress was studied in cotyledonary stage of MDE of two genotypes: Cadeli (D), and Viking (V), previously reported to exhibit contrasting leaf proteome responses under drought. 2D-DIGE revealed 156 representative protein spots that have been selected for MALDI-TOF/TOF analysis. Sixty-three proteins have been successfully identified and divided into 8 functional groups. Data are available via ProteomeXchange with identifier PXD024552. Eight selected protein accumulation trends were compared with RT-qPCR. Biomass accumulation in treated D was significantly higher (3-fold) than in V, which indicate D is resistant to osmotic stress. Cultivar D displayed resistance strategy by the accumulation of proteins in energy metabolism, redox homeostasis, protein destination and signaling functional groups as well as by high ABA and active cytokinins (CKs) contents. In contrast, V protein profile displayed high requirements of energy and nutrients with a significant number of stress-related proteins and cell structure changes accompanied by quick down-regulation of active CKs, as well as salicylic and jasmonic acid. Genes suitable for gene-targeting that showed significantly higher expression in treated samples were identified as phospholipase D alpha, peroxiredoxin antioxidant and lactoylglutathione lyase. MDE proteome profile has been compared with leaf proteome evaluated in our previous study. Different mechanisms to cope with osmotic stress were revealed between the genotypes studied. This proteomic study is the first step to validate MDE as a suitable model for follow-up research on characterization of new crossings, and can be used for pre-selection of resistant genotypes.